PEMBERDAYAAN PEMBELAJARAN AL-QUR’AN BERBASIS PENDEKATAN ABCD DI TPA NURUL HUDA DESA MENURAN, SUKOHARJO - Abdullah Muhammad Yahya; Febryan Hidayat; Zainal Abidin (Institut Islam Mamba'ul 'Ulum Surakarta, 2025)
This community service programme was motivated by the finding that the learning process at Nurul Huda TPA was still dominated by the talqin method, causing students to often feel bored and unmotivated to learn. The lack of variety in learning methods had an impact on the uneven ability to read the Qur'an and a lack of understanding of the correct practice of worship. Therefore, this activity was carried out with the aim of improving the ability to read and write the Qur'an, improving pronunciation through tahsin, and equipping students with an understanding and practice of proper prayer. In addition, this activity aimed to foster interest in learning through fun learning methods based on stories and educational games. The programme was implemented over a month using a descriptive approach and the principles of Asset-Based Community Development (ABCD), which emphasises the empowerment of local assets such as teaching staff, students, and the mosque environment. The results of the activity showed an improvement in the ability to read and write the Qur'an, improved pronunciation of Hijaiyah letters, and increased student participation in prayer practices. The learning atmosphere became more active and enjoyable. In conclusion, the variety of learning methods combined with the ABCD approach was able to significantly improve the motivation, abilities, and religious character of the students.